CORAK TARBAWI DALAM PENAFSIRAN SYEKH ‘ABD AL-QADIR AL-JILANI - Badrudin, Badrudin (MAGHZA, 2017)
This research was inspired by the condition of the world today dominated by secular education. The danger of secular education for human life is producing generations who eliminate religious principles in their life. To examine the concept of Educational Exegesis (Tafsir Tarbawi) the contents away from the secular need to be empowered. Research products offered the format of important themes in the study of Quranic Educational exegesis. The restriction of problems of this research is the problem of education in view of the interpretation of Sheikh ‘Abd al-Qa>dir Ji>la>niy. In this study the author used the following methodology: 1) Paradigm of thematic analysis, which collecting the verses in Educational themes. Then analyze and summarize as a reflection of the Quran answers to the mentioned problems, 2) Content analysis. The orientation is inductive reasoning, the conclusion of a general nature to a special nature. The results of this study indicate those who studied in the view of Shaykh ‘Abd al-Qa>dir Ji>la>niy is preferred. Interpretations of the Educational verses as follows: The goal of education-oriented by Shaykh ‘Abd al-Qa>dir Ji>la>niy was towards cleansing the heart or purification of the soul, this is a high degree in the educational process.  The material of thought that developed by  Shaykh  ‘Abd al-Qa>dir  Ji>la> ni about educational stated behavior and certain obligations that must be considered by the teacher in treating his pupils. Teaching methods used by Shaykh ‘Abd al-Qa>dir Ji>la>niy often give back in the name of Allah (Quran) and The Tradition of the Prophet in exposure-presentation. Then he showed a tremendous emphasis on the importance of firmness and constancy in the oneness of Allah.